Potensi biofisik ekosistem mangrove untuk ekowisata di kampung parambu, kabupaten jeneponto - Rajab, Muhammad Arhan (Jurnal Kepariwisataan dan Hospitalitas; Vol 4 No 1 (2020): Vol.4,No.1,2020DO - 10.24843/JKH.2020.v04.i01.p03, 2020)
This research was conducted in Kampung Parambu, Kab. Jeneponto in February-March 2020. This study aims to (1) determine the potential of the mangrove ecosystem in Kampung Parambu, Kab. Jeneponto; (2) knowing the potential of mangrove ecosystem stands in Kampung Parambu, Kab. Jeneponto. The approach used is survey research. The data obtained were analyzed descriptively and quantitatively. The results obtained from the potential of mangrove ecosystems in Parambu Village are dominated by mangrove species Rhizophora sp. with a total area of ??10 Ha (6 Ha is good, 3 Ha is slightly damaged and 1 Ha is heavily damaged) while the potential of mangrove stands is on average 20,000 trees / ha and volume 648.41 m3 / ha. These conditions illustrate that the existence of mangrove ecosystem resources in Kampung Parambu, Kab. Jeneponto has enough potential to be utilized by the local community. Therefore, policies in managing mangrove ecosystem resources need to consider biophysical aspects for further development. Keywords: potential, biophysical, ecotourism, mangrove